Local Metric Dimension of Certain Operation of Generalized Petersen Graph - Tadjuddin, Nur Fahri; Nikbakht, Samaneh (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2025)
A subset W of V(G) is called a local resolving set of G if r(u│W)≠r(v│W) for every two adjacent vertices u,v∈V(G). The smallest cardinality of all local resolving sets in G is called the local metric dimension of G, denoted by lmd(G). The local resolving set of G with cardinality lmd⁡(G) is called a local basis of G. In this paper, we present a novel study, a topic that has not been extensively explored in previous research, on the local metric dimension of certain operation of generalized Petersen graph sP_(n,1) and determine the lower and upper bounds of lmd(sP_(n,m)) with n≥3, s≥1, and 1≤m≤⌊(n-1)/2⌋. We also show that the lower bound is sharp.Keywords: Generalized Petersen graph; Local metric dimension; Local resolving set. AbstrakSuatu subset W dari V(G) dikatakan himpunan pembeda lokal dari G jika r(u│W)≠r(v│W) untuk setiap dua titik bertetangga u,v∈V(G). Kardinalitas terkecil dari semua himpunan pembeda lokal di G disebut dimensi metrik lokal dari G, dinotasikan lmd(G). Himpunan pembeda lokal G dengan kardinalitas lmd(G) disebut basis lokal dari G. Pada artikel ini, disajikan sebuah studi baru, topik yang belum dieskplorasi secara ekstensif dalam penelitian sebelumnya, tentang dimensi metrik lokal dari graf hasil operasi tertentu untuk graf Petersen diperumum sP_(n,1) dan menentukan batas atas dan bawah dari lmd(sP_(n,1)) dengan n≥3, s≥1, dan 1≤m≤⌊(n-1)/2⌋. Kami juga menunjukkan bahwa batas bawah tersebut tajam.Kata Kunci: Graf Petersen diperumum, Dimensi metrik local; Himpunan pembeda local. 2020MSC: 05C12, 05C76